UNDERSTANDING GEN Z TAX COMPLIANCE BEHAVIOUR - Ervina Kurnia; Khomsiyah Khomsiyah (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study is to examine the perceptions of Z generations related to peer group influence, digitalization tax service orientation, tax knowledge, and social media platform influence. Changes traditional paradigm of tax compliance in order to improve voluntary tax compliance in Z generation. This research method is a survey method using electronic questionnaires. The respondents (sample) of this study are tax payer with have age under 28 years old. Data was analyzed by using multiple regression analysis. The results of a survey of 142 tax payers indicate that peer group, digitalization tax system, tax knowledge and social media increase tax payer compliance. The contribution of this work is a more brief and straightforward understanding of behavioral accounting, primarily related to the tax compliance of generation Z. In contrast to the overarching goal of prior research , the current study analyzes the impact of tax payer compliance and the other analyze gen Z consumption behavior.